Initial design principles for establishing a learning community for public health professionals through authentic e-learning. (2015) - Vesper, James L.; Herrington, Jan; Kartoğlu, Umit; Reeves, Thomas C.
The storage, transportation and distribution of time and temperature sensitive pharmaceutical products (TTSPPs) such as vaccines within the appropriate temperature conditions are important public health concerns. The personnel who handle pharmaceutical products must have high levels of expertise so they can take actions to ensure that the TTSPPs are not negatively affected by sub-standard practices. This paper describes the first phase of a multi-year educational design research project designed to enhance expertise in the field of pharmaceutical cold chain management. The paper describes the process of developing design principles to guide the conceptualisation and prototyping of authentic e-learning capable of enabling public health personnel to develop the skills required for effective pharmaceutical cold chain management and to establish a learning community extending beyond the course. Five design principles are shared along with examples of how they were instantiated in the prototype e-learning.